Using tracking data from matches and training situations - Sampaio, Jaime (2020)
The process of preparing to perform at the highest level of competition in football is probably one of the most complex tasks to endeavour under the scope of Sports Sciences. This clear complexity might be one of the major causes explaining why there is still a strong societal believe that science has little to offer to help improving performance in such activities.